2013
DOI: 10.1155/2013/519080
|View full text |Cite
|
Sign up to set email alerts
|

Nexfin Noninvasive Continuous Hemodynamic Monitoring: Validation against Continuous Pulse Contour and Intermittent Transpulmonary Thermodilution Derived Cardiac Output in Critically Ill Patients

Abstract: Introduction. Nexfin (Bmeye, Amsterdam, Netherlands) is a noninvasive cardiac output (CO) monitor based on finger arterial pulse contour analysis. The aim of this study was to validate Nexfin CO (NexCO) against thermodilution (TDCO) and pulse contour CO (CCO) by PiCCO (Pulsion Medical Systems, Munich, Germany). Patients and Methods. In a mix of critically ill patients (n = 45), NexCO and CCO were measured continuously and recorded at 2-hour intervals during the 8-hour study period. TDCO was measured at 0–4–8 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 31 publications
2
48
0
2
Order By: Relevance
“…While Broch et al [22] demonstrated that the Nexfin system allows CO estimation in cardiac surgery patients with a percentage error of \30 % when compared with transpulmonary thermodilution, higher percentage errors between 38 % and 58 % were reported in other clinical studies evaluating the system in cardiac surgery patients in comparison with pulmonary artery or transpulmonary thermodilution [23][24][25][26]. In 45 mixed ICU patients, Ameloot and colleagues [27] revealed a percentage error of 36 % between Nexfin-CO and CO determined by transpulmonary thermodilution. In another study in medical ICU patients, Monnet et al [28] however observed a percentage error of 57 % when comparing Nexfin-derived cardiac index with transpulmonary thermodilution measurements.…”
Section: Discussionmentioning
confidence: 98%
“…While Broch et al [22] demonstrated that the Nexfin system allows CO estimation in cardiac surgery patients with a percentage error of \30 % when compared with transpulmonary thermodilution, higher percentage errors between 38 % and 58 % were reported in other clinical studies evaluating the system in cardiac surgery patients in comparison with pulmonary artery or transpulmonary thermodilution [23][24][25][26]. In 45 mixed ICU patients, Ameloot and colleagues [27] revealed a percentage error of 36 % between Nexfin-CO and CO determined by transpulmonary thermodilution. In another study in medical ICU patients, Monnet et al [28] however observed a percentage error of 57 % when comparing Nexfin-derived cardiac index with transpulmonary thermodilution measurements.…”
Section: Discussionmentioning
confidence: 98%
“…Research on new risk factors for hypotension and bradycardia is on going, using low-invasive methods of haemodynamic monitoring [21]. Easily measurable risk factors for adverse circulatory consequences of spinal anaesthesia are individual patient characteristics, e.g., age, gender, body mass or its index (BMI).…”
Section: Discussionmentioning
confidence: 99%
“…The opinions regarding the device are positive regarding the reliability of arterial pressure measurements [25−27]; however, the agreement of the Nexfin-based CO and SVR measurements is assessed cautiously, although the majority of authors rate it as quite good or good [21,28,29]. Another limitation is the arbitrarily assumed central venous pressure value and the basing of SVRI calculations on it.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The technique is not applicable in low flow in the finger arteries, hypothermia, or peripheral oedema. ClearSight CO has been studied in cardiac surgical patients against PAC and PiCCO and has demonstrated a limited accuracy and precision and a high percentage error (weighted average of 41%) [83][84][85][86][87][88][89][90][91], but reliably track preload-induced changes in CO [92][93][94]. ClearSight was less accurate in patients with low CO, hypothermia and high SVR but performed better in patients with high CO [95].…”
Section: Clearsight System (Edwards Lifesciences® -Usa)mentioning
confidence: 99%